Black vs white owned new venture performance: A study of mediating effects - Mayank Jaiswal (New England Journal of Entrepreneurship (NEJE), 2018)
Purpose - The purpose of this paper is to move beyond individual level characteristics of founders to explain the performance gap between white and black majority owned new ventures. It specifically investigates three potential mediators: demographic characteristics of venture's location, financial size of the venture and its credit riskiness. Design/methodology/approach - The Kauffman Firm Survey, a longitudinal data set of 4,928 new ventures started in the USA in 2004, has been utilized in this paper. Pooled OLS and Logit regression models were employed for direct effects. Mediation effects were tested using two different approaches: the Baron and Kenny approach and decomposition analysis. Findings - The paper finds that the financial size and credit riskiness mediate the relationship between majority race ownership and the performance of a venture. Research limitations/implications - The data were collected for a single cohort (2004) of nascent firms; furthermore, the sample draws from firms based in the USA. Future studies could replicate this research utilizing samples of different cohorts and from other parts of the world. Practical implications - The paper provides important guidance to policy makers. In general, to reduce the performance gap between black and white owned ventures, providing access to subsidized assets, capital and credit could be very helpful. Originality/value - Past research suggests that the majority race ownership of a new venture impacts its performance and attributes these differences to heterogeneous endowments, usually of the primary owner. In this paper, analyses are conducted at multiple levels and new mechanisms through which the internal resources and capabilities of a new venture mediate the relation are discovered.
Keywords: 650; Diversity; Entrepreneurship; New ventures